STRATEGIC PLANNING AND DEVELOPMENT PROCESS OF MUNICIPAL EDUCATION IN UKRAINE - Kulchytska , N.Ye. (The actual problems of regional economy development, 2019)
The article explores the theory of state strategic management at the regional level. The world experience of territorial economy development efficiency is studied and strategic planning is distinguished on this basis. It is argued that the theory of public strategic management is similar to the strategic management of any company. A model of strategic management process is developed. The key elements of the strategic planning system in Ukraine are grounded. The levels of the state strategic planning system are separated. The structure of directions of activity of municipal education in ATS is substantiated. The purpose of this article was to study the socio-economic development of the municipality in the context of strategic planning of the socio-economic development of the region. The methods of analysis, historical comparison, empirical research are used in the article, the emphasis is on the similarity of the theory of state strategic management and strategic management. The doctrines, theories and concepts of state regulation of economy and socio-economic development are studied, and therefore attention is drawn to the lack of such definition as state strategic management, municipal education that would bring a new vision for balanced development of society and economy. and justification of its stated goals, steps and functions. The practical significance of the study is that the results of the study can be used in the activities of local governments. The results of the study are: development of integrated strategies for regional development, municipal education; organization of implementation of strategic plans; coordination of actions on realization of strategic tasks; motivation to achieve strategic results; control over the process of implementation of the strategy of regional socio-economic development.